A taxonomic revision of the genus Synodontis (Pisces, Mochokidae) in Southern Africa - White, Peter Nevins (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1987)
The alpha taxonomy of the southern African Synodontis is reviewed, based on the analysis of 48 characters. The previously descriptive characters of barbel branching and humeral process shape are compared by various quantitative methods. The variation in colour pattern is recorded with the aid of detailed line drawings. The definitions of head length, head width and humeral process length are altered slightly from their traditional descriptions to ensure greater consistency and precision in measurement. New characters include the size of the caudal fork, the number, shape and arrangement of the premaxillary teeth, and two measurements between the cranium and pectoral girdle. Both uni- and bivariate methods are used to record and compare the intraspecific variation of each character. Principal components analysis of 19 morphometric characters is used to assess the degree of similarity of nine allopatric populations of S. zambezensis. Ten species are recognized from the study area, two of which are described as new: S. nebulosus Peters 1852, S. zambezensis Peters 1852, S. nigromaculatus Boulenger 1905, S. njassae Keilhack 1908, S. woosnami Boulenger 1911, S. macrostigma Boulenger 1911, S. leopardinus Pellegrin 1914, S. thamalakanensis Fowler 1935, S. macrostoma sp.n. and S.vanderwaali sp.n. A key to their identification is provided. Characters are discussed in terms of their contribution to the identification of the southern African species and, where possible, suggestions made concerning the value of these characters to the taxonomy of the genus as a whole. The rejection of certain characters previously used in Synodontis keys is discussed and alternatives proposed. The state of southern African Synodontis taxonomy is assessed and recommendations for future research are given
Keywords: Mochokidae -- Africa, Southern -- Classification; Synodontis -- Africa, Southern -- Classification